2009
DOI: 10.1016/j.ejcts.2009.06.045
|View full text |Cite
|
Sign up to set email alerts
|

Gene therapies for pulmonary hypertension—from experimental trials to bedside aspects

Abstract: Accompanying the continuously deepening understanding of the mechanism of pulmonary hypertension that many genes are found to be aetiologically involved in its development, burgeoning literature manifest that gene therapies aimed at correcting these genetic defects have the ability to restore deficient pulmonary gene expression, over-express biologically active gene products, reverse established disease and regenerate pulmonary vasculature, and may constitute a promising therapeutic strategy for pulmonary hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 191 publications
0
1
0
Order By: Relevance
“…Recently, several studies by independent groups have shown the potential therapeutic benefit of modulating a variety of molecular targets using gene therapy [7, 8]. For instance, endothelial NOS, prostacyclin synthase or BMPR2 have been successfully modulated in the pulmonary vasculature leading to improved hemodynamics in animal models of PH [911]. …”
Section: Introductionmentioning
confidence: 99%
“…Recently, several studies by independent groups have shown the potential therapeutic benefit of modulating a variety of molecular targets using gene therapy [7, 8]. For instance, endothelial NOS, prostacyclin synthase or BMPR2 have been successfully modulated in the pulmonary vasculature leading to improved hemodynamics in animal models of PH [911]. …”
Section: Introductionmentioning
confidence: 99%